2022
DOI: 10.1111/cod.14249
|View full text |Cite
|
Sign up to set email alerts
|

The use of carvone in consecutive patch testing

Abstract: Background: Carvone (l-carvone) is a mint-tasting flavour additive that most of us is exposed to and can cause allergic contact reactions.Objectives: To analyse the frequency and the relevance of positive carvone reactions in a dermatitis population.Method: A retrospective analysis of dermatitis patients consecutively tested with carvone from 2017 to 2021. Data were retrieved from the department's patch-test database.Results: Of 3554 patients tested with carvone, 28 (0.79%) had a positive reaction.Carvone-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The literature has highlighted these substances as allergens responsible for cheilitis. 2,30 A recent study from Australia reported a high rate of relevant reactions to peppermint oil (5 out of 61) and spearmint (4 out of 61). However, we did not find positive reactions to menthol and peppermint oil in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has highlighted these substances as allergens responsible for cheilitis. 2,30 A recent study from Australia reported a high rate of relevant reactions to peppermint oil (5 out of 61) and spearmint (4 out of 61). However, we did not find positive reactions to menthol and peppermint oil in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Mint flavours, such as menthol, peppermint oil, spearmint oil and L‐carvone are commonly used in toothpastes. The literature has highlighted these substances as allergens responsible for cheilitis 2,30 . A recent study from Australia reported a high rate of relevant reactions to peppermint oil (5 out of 61) and spearmint (4 out of 61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64 In light of evidence that apiole may have abortion-inducing effects, it is recommended that apiole-rich essential oils be avoided during pregnancy and breastfeeding. 65,66 There are reports of carvone-associated contact allergenicity, [67][68][69][70][71][72][73][74][75][76][77][78] including several due to use of carvonecontaining toothpastes and other personal care products. A different concern arose from 1 small observational study in Turkey of patients with thyroid disease in which a decrease in thyroid hormone levels and an increase in thyroid nodule volumes were detected for those consuming 100-g dill.…”
Section: Safetymentioning
confidence: 99%
“…There are reports of carvone-associated contact allergenicity, 67–78 including several due to use of carvone-containing toothpastes and other personal care products. A different concern arose from 1 small observational study in Turkey of patients with thyroid disease in which a decrease in thyroid hormone levels and an increase in thyroid nodule volumes were detected for those consuming 100-g dill 79 .…”
Section: Safetymentioning
confidence: 99%